A bibliometric analysis of research on fish and floristic diversity: Trends and themes - Khalid Awadh Al-Mutairi (Journal of Fisheries, 2024)
Research on the relationship between fish and floristic diversity has been limited by narrow scopes, inconsistent methodologies, and geographic biases, resulting in fragmented insights. This study presents a comprehensive bibliometric analysis on the relationship between fish diversity and floristic diversity, spanning nearly six decades from 1965 to 2024. Using the Scopus database, 47 publications were identified based on the presence of the keywords "fish" and "floristic diversity" in article titles, abstracts, and keywords. The analysis reveals a gradual increase in publications over time, with notable peaks corresponding to heightened awareness of biodiversity conservation. The research themes identified include habitat provision, ecosystem resilience, impact of environmental change, and the role of invasive species. The study highlights the importance of integrating conservation strategies that protect both fish and plant diversity to maintain ecosystem health and resilience. The findings also point to regional and taxonomic specificity as critical areas for future research, particularly in climate change and habitat alteration. This bibliometric review provides valuable insights into the evolution of this field and identifies gaps and opportunities for further investigation. Therefore, the study underscores the critical interdependence between fish and floristic diversity within ecosystems, a relationship that both natural processes and anthropogenic influences have shaped over time. The findings suggest that conservation efforts must adopt a more integrated approach, recognizing the mutual dependencies between different forms of biodiversity. This approach will be essential for mitigating the adverse effects of human activities on ecosystems and ensuring the long-term sustainability of both fish and plant communities.